Emergency medicine pharmacists’ interventions in the tertiary hospitals’ emergency departments in Malaysia - Hock Peng Koh; Haliza Ab Jalal; Yee Ping Koo; Mary Siew Yng Chen; Manimegahlai Selvaratanam; Anaanthan Bhuvanendran Pillai; Wai Kit Wong; Xin Nee Guee; Sherene Su Ann Tan; Shirlyn Tan; Lih Jiuan Teh; Rosalind Guen Lin Sia (Journal of Pharmaceutical Policy and Practice)
Background: The emergency medicine (EM) pharmacist is an integrated part of the Emergency Department (ED) interdisciplinary team in many countries, including Malaysia. The presence of EM pharmacists in the ED has positively impacted patient outcomes. Data on EM pharmacists’ interventions is scarce in the Asian region. In Malaysia, data on interventions done by EM pharmacists in the EDs was unavailable. This study aimed to assess the type of interventions done by EM pharmacists in the ED of tertiary public hospitals in Malaysia.Methods: This cross-sectional, multicenter study involved EM pharmacists from 14 tertiary hospitals in Malaysia. All accepted interventions done by EM pharmacists in the ED for patients admitted to the Red (critical) and Yellow (semi-critical) zones from January to June 2022 were extracted from the Clinical Pharmacy Report Form. All data were analyzed descriptively.Results: The EM pharmacists documented 1659 accepted interventions on 1584 patients during the study period. Inappropriate regimens (n = 1117, 67.3%) and incomplete prescriptions (n = 339, 20.4%) were the main categories of accepted interventions in ED. Inappropriate drug (n = 574, 34.6%), dose (n = 292, 17.6%), and frequency (n = 176, 10.6%) were the top three subcategory interventions documented under inappropriate regimens. Antimicrobials, antihypertensives, and proton pump inhibitors were the commonest drug intervened under the categories of inappropriate drug intervention. There were 272 (16.4%) accepted interventions on high-alert medications (HAMs). Insulin, enoxaparin, and noradrenaline were the most intervened HAMs.Conclusion: Inappropriate treatment regimens were the most common intervention category done by EM pharmacists in Malaysia. The significant number of interventions done by EM pharmacists demonstrated the importance of EM pharmacists as integral members of the EM team. This data can help improve the quality of clinical pharmacy services in the ED and is important for the future expansion of clinical pharmacy services in all EDs across Malaysia, neighbouring countries, and other developing countries.